4H-Thieno[3, 2-c]chromene based inhibitors of Notum Pectinacetylesterase. Issue 4 (15th February 2016) - Han, Qiang; Pabba, Praveen K.; Barbosa, Joseph; Mabon, Ross; Healy, Jason P.; Gardyan, Michael W.; Terranova, Kristen M.; Brommage, Robert; Thompson, Andrea Y.; Schmidt, James M.; Wilson, Alan G.E.; Xu, Xiaolian; et al.
Graphical abstract: A group of small molecule thienochromenes inhibitors of Notum Pectinacetylesterase are described. We developed SAR on three series based on carbon, oxygen and sulfur replacement of the 5-position. In each series, highly potent Notum Pectinacetylesterase inhibitors were identified. Abstract: A group of small molecule thienochromenes inhibitors of Notum Pectinacetylesterase are described. We developed SAR on three series based on carbon, oxygen and sulfur replacement of the 5-position. In each series, highly potent Notum Pectinacetylesterase inhibitors were identified.